Estudo das propriedades estruturais, eletrônicas e ópticas do tetraborato de magnésio (MgB4O7) e do defeito antissítio em compostos Bi12MO20 (M=Ge,Si,Ti) utilizando cálculos de primeiros princípios - Oliveira, Tarsila Marília de (2017)
This work represents a theoretical study, based on density functional theory (DFT), on structural, electronic and optical properties of magnesium tetraborate (MBO, MgB 4 O 7 ) compound and of antisite Bi M O 4 defect in Bi 12 MO 20 (BMO, M=Ge, Si, Ti) compounds. All calculations have been realized by linear augmented plane wave (LAPW) method implemented in Wien2k computer code. The relaxation of atomic positions and lattice parameters has been performed using LDA (MBO) and PBE-GGA (BMO) exchange- correlation (XC) functional. Electronic structure, optical properties and chemical bonds were investigated using the semi-local XC potential of Tran and Blaha (TB-mBJ), which signiﬁcantly improved the band gap description and optical properties of studied systems. The thesis is divided in two parts. The ﬁrst refers to study of magnesium tetraborate in pure form. Electronic structure calculations predicted a 9.58 eV band gap value, quite close to the value determined in the similar compounds. The electronic structure around the band gap is found to be dominated by the O 2p-states and 2p-states of the boron ion with trigonal coordination with neighbouring O‘s. Optical properties were analysed in terms of complex dielectric tensor which imaginary part is directly proportional to the optical absorption spectra. The latter is found to exhibit two prominent peaks. The lower energy peak originates from electron transitions within the trigonal B−O 3 structural group. Refractive index, reﬂectivity, extinction coeﬃcient and energy loss were analysed in ultraviolet range (up to 40 eV) and all calculated optical properties are found to be anisotropic. The second part presents a theoretical study upon the antisite defect Bi M O 4 in sillenites compounds, which consists of wrong occupation of the M site by the Bi ion. Calculations were performed ﬁrstly for the pure compounds. The crystal structure has been computatio- nally optimized and the band gaps found to be 3.39 eV, 3.35 eV and 3.37 eV for the BGO, BSO and BTO respectively. These values are in very good agreement with experimental data. Defects were investigated in q=-1,0,1 charge states. Electronic structure calculations demonstrated that the antisite defect introduces an energy band inside the gap formed by O 2p- and 6s- states of Bi M ion. This band occupation is directly related to the defect charge state. The neutral defect presents a semi populated band, the positively defect adonor band and the negatively defect an acceptor band. The Bader analysis conﬁrmed that the electron added or removed from the host system is always localised in the area of the defect. The analysis of the defect formation energies demonstrated that the neutral defect is energetically favourable, and thus dominates the lowest thermal state of the sillenites (also called colour state). On the other hand, the charged defects are predominant in the so-called transparent thermal state of the sillenites. From the results, it was possible to associate the presence of the antisite defect with important properties observed in the BMO crystals, such as: (1) explanation of the charge mobility required to produce the photorefractive eﬀect; (2) reversible transitions between the thermal states and (3) photocromic eﬀect in sillenites.